Character Education in a Children’s Short Story Book entitled “Linda has a Papaya Garden” - Ayu Anindia Hizraini; Retno Winarni; Sri Yamtinah (STAI Hubbulwathan Duri, 2022)
This study aims to describe structures and the values of character education in the children's storybook